2022
DOI: 10.14704/web/v19i1/web19187
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Mass Media in Social Construction of the Reform of Indonesia Bureaucracy

Abstract: Mass media development, both in the form of content and technology, has been promoting the implementation of bureaucratic reform in Indonesia during the last fifteen years. In the world, it generally begins with the spirit of transparency, the spirit of accountability, the spirit of participatory, to the spirit of reforming the state bureaucracy. In Indonesia, these four subjects also appear, at least since the reformation era, mass media gives a new color in the overall Indonesian bureaucracy activity since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The public perception of the condition of the bureaucracy is influenced by the policy narrative that is built in the bureaucratic reform process. Policy narrative is a crucial point in the bureaucratic reform process (Boon and Verhoest, 2018;Poernomo et al, 2022;Pratama and Manurung, 2022). In the Indonesian context, Turner et al's research (2022) explains that bureaucratic reform is a priority narrative and government of developing countries such as Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public perception of the condition of the bureaucracy is influenced by the policy narrative that is built in the bureaucratic reform process. Policy narrative is a crucial point in the bureaucratic reform process (Boon and Verhoest, 2018;Poernomo et al, 2022;Pratama and Manurung, 2022). In the Indonesian context, Turner et al's research (2022) explains that bureaucratic reform is a priority narrative and government of developing countries such as Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Policy narratives related to bureaucratic reform are urgent to study in assessing how bureaucratic reform policies are implemented, especially the widespread use of mass media has a role in influencing the policy-making process. In a study, Poernomo et al (2022) found that mass media has become a platform that is able to influence the setting of the policy agenda. The development of mass media, both in the form of content and technology, has encouraged the implementation of bureaucratic reform in Indonesia over the past fifteen years.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors in the potential for violations in the 2024 election include the neutrality of civil servants, the neutrality of village heads, updating of voter data, and changes in the number of votes. This challenge strengthens organizational and human resources to be very important, especially in terms of implementing bureaucratic reforms (Poernomo et al, 2022). This challenge also spurred the author to see how bureaucratic reforms have been carried out in several countries (Abidin & Effendi, 2022).…”
Section: Introductionmentioning
confidence: 99%